2022
DOI: 10.3892/etm.2022.11210
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑200a‑3p and GATA6 are abnormally expressed in patients with non‑small cell lung cancer and exhibit high clinical diagnostic efficacy

Abstract: Lung cancer is one of the main threats to human health. Survival of patients with lung cancer depends on timely detection and diagnosis. Among the genetic irregularities that control cancer development and progression, there are microRNAs (miRNAs/miRs). The present study aimed to investigate the expression patterns of miR-200a-3p and transcription factor GATA-6 (GATA6) in peripheral blood of patients with non-small cell lung cancer (NSCLC) and their clinical significance. The expression patterns of miR-200a-3p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Recently, some scholars conducted relevant studies on the role of miR-200a-3p in non-small cell lung cancer [ 25 ], cervical cancer [ 26 ], bladder cancer [ 27 ], and other tumors, establishing the regulatory mechanism of miR-200a-3p in these tumors. The results showed different mechanisms of action and phenotypic effects of miR-200a-3p in different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some scholars conducted relevant studies on the role of miR-200a-3p in non-small cell lung cancer [ 25 ], cervical cancer [ 26 ], bladder cancer [ 27 ], and other tumors, establishing the regulatory mechanism of miR-200a-3p in these tumors. The results showed different mechanisms of action and phenotypic effects of miR-200a-3p in different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Many miRNAs, such as miR‐21 [ 101 ], miR‐126 [ 102 ], and miR‐200a‐3p [ 103 ], have been demonstrated to be highly expressed in LC patient serum compared with serum from healthy individuals. They can therefore be used as serological markers for LC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…3 Studies demonstrated that the metastasis of LUAD is associated with the downregulation of GATA6 with prognostic value. 4 EZH2 was found up-regulated expression in LUAD cells in promoting the invasiveness of tumor cells. 5 Hence, it is of great importance to uncover mechanisms of LUAD for exploring more biomarkers and developing novel therapies.…”
mentioning
confidence: 93%
“…Identifying the prognostic molecular markers of LUAD can provide some value for the clinical diagnosis of LUAD 3 . Studies demonstrated that the metastasis of LUAD is associated with the downregulation of GATA6 with prognostic value 4 . EZH2 was found up‐regulated expression in LUAD cells in promoting the invasiveness of tumor cells 5 .…”
Section: Introductionmentioning
confidence: 99%